Upaya Modernisasi Klepon sebagai Produk Kuliner Tradisional untuk Menyesuaikan dengan Tren Kekinian - Muhammad Irfan; Lilik Hariyanto; Kezia Elsty; Aan Nurhasanah; Rahmat Kusnedi (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to explore the process of transforming traditional Javanese food into modern dishes by adopting a culinary creativity approach and considering today's consumer preferences. One of the dishes that is the main focus of this study is Klepon Lava Cake, an innovation that combines elements of traditional Indonesian food, namely klepon, with a modern dessert concept that is popular among the younger generation. This study seeks to preserve traditional Javanese food in a more attractive, creative, and relevant way, so that it can attract the interest of today's consumers, especially young people who have different tastes and lifestyles than previous generations. Theoretically, this study contributes to the field of gastronomy and culinary innovation by providing new insights into ways that can be applied to develop tradition-based food products to remain relevant in the modern culinary market. Through an understanding of culinary creativity and how to combine local ingredients with modern cooking techniques, this study shows that culinary traditions can adapt without sacrificing their cultural values. Practically, the results of this study can provide benefits for culinary entrepreneurs, especially in designing tradition-based culinary products that have market appeal and can compete in the increasingly growing food industry. By combining traditional and innovative elements, culinary entrepreneurs can create products that not only preserve cultural heritage but also meet the needs and desires of today's consumers. This research shows that creativity in processing traditional foods can be key to introducing Indonesian cuisine to the global market. Furthermore, this study also considers the importance of consumer preferences in creating culinary products that are acceptable to modern society.